PENGARUH TERAPI MEWARNAI TERHADAP KENYAMANAN HOSPITALISASI PADA ANAK USIA PRASEKOLAH DI RSUD WALED KABUPATEN CIREBON TAHUN 2018 - Tantri Maulani Putri; Dwiyanti Purbasari; Thia Octiany (Jurnal Kesehatan Mahardika, 2019)
Children who experience hospitalization in 2017 reached 2502 at Waled Public Hospital Cirebon. The impact of hospitalization gives rise to stress, insecurity and discomfort (Oktiawati, 2017). Coloring therapy is effective for improving child comfort during hospitalization. This study was conducted to know the effect of colour therapy on the comfort of hospitalization in preschoolers at Waled Public Hospital Cirebon. The design used was quasy experiment with pre-post control group design approach. The number of samples of 32 children, with incidental sampling technique. The comfort instrument used is an observation sheet that refers to the Intermountain Healthcare Comfort Assessment that has been modified with the value of r table validity > 0.7293 and reliability testing shows that the p value < alpha means significant kappa test results.This research carried out in the anyelir ward of Waled Public Hospital Cirebon in June-July 2018. The results showed that 16 respondents experienced comfort in the intervention group. The comfort value of hospitalization after intervention has increased (22.8750) with a standard deviation of 0.80623 and the lowest comfort of 21.00 and the highest of 24.00. The results of statistical tests with paired t-test showed that there was an effect of coloring therapy on the comfort of hospitalization in preschool-aged children in the intervention group (p-value = 0,000 α = 0.05).This research is expected to become the basis for further researchers on the development of nonpharmacological therapy by replacing variables such as growth and development or comparing with other techniques.